Teachers Understanding Towards COVID-19: A Case of Dhankuta Multiple Campus, Dhankuta, Nepal - Parajuli, Kewal Ram; Linkha, Tika Ram (Rupantaran: A Multidisciplinary Journal, 2020)
Teacher educators are playing a significant role in managing pandemic situation at various ways. Their role is important to raise public awareness about epidemic and pandemic diseases, like COVID-19. It is mainly due to education and educators are to be considered as an initiator of changes at community level. Their preparedness, understanding, practices and participation can be reliable way to measure the impact of COVID-19 in Dhankuta district. In this context, the focus of this paper is to estimate teachers' knowledge, understanding and practices to preventive measures of COVID-19. In addition, the paper has also intended to analyze the opportunities and challenges that lockdown has bought in their academic environment. For this purpose, 51 teachers were chosen from Dhankuta Multiple Campus using proportionate stratified random sampling (SRS) method with covering gender and faculties. Web based cross sectional research design was applied and some of the variables, like knowledge about COVID-19, adoptive practices, challenges faced in academic environment and reduction strategy were considered to collect and analyze data. The findings of this paper indicate that the mean score of overall knowledge and practices are 6.90 and 6.4 respectively and 94.1 % faces academic challenges. Meantime, the respondent reported that hotels and markets were more vulnerable places as compared to other economic sectors. Their responses ranked such as use of mask, sanitizer, distance maintain, lockdown, and quarantine were some of the ways to prevent COVID-19. However, 70.6 % teachers were involved in online classes, e-library and continuing their academic activities. This paper concludes that the pandemic of COVID-19 has also created a new environment in teaching-learning with the application of ICT in pedagogy in changing situation.